Sulodexide efficacy in the treatment of patients with chronic lower limb vein diseases of C1-C3 clinical classes according to CEAP - S. E. Katorkin; M. A. Melnikov; P. F. Kravtsov (Амбулаторная хирургия, 2019)
Aim of the study. To evaluate  the clinical efficacy of sulodexide in the daily dosage of 500 LSU in patients with chronic lower limb vein diseases  of clinical classes C1-C3 according to CEAP.Patients and methods.  This study included 35 patients with chronic C1-C3 CEAP lower limb vein disease  who took 500 LSU of Sulodexide for 90 days. In order to evaluate the effectiveness of the treatment we used: a questionnaire to assess the quality of patient’s life with chronic venous insufficiency  CIVIQ 20; visually – analogue scale of pain assessment VAS; clinical scale of venous diseases VCSS severity assessment; measuring the circumference of the limbs on the hip and shin.Results of the study. The study was completed  by 32 patients. As a result of the performed  treatment the convulsive syndrome in calf muscles completely  regressed, though on the first visit it was registered in 22,4% of patients (p  =  0,0481), the frequency of complaints  about severity and fatigue in the lower limbs at static loads decreased  significantly from 28,1% to 9,6% (p  = 0,2414). The circumference of the femur in the middle third of the limb decreased  from 53.7 cm to 51.1 cm (p<0.05), in the middle third of the tibia from 36.8 cm to 33.8 cm (p<0.05) and in the lower third of the tibia from 23.4 cm to 21.5 cm (p<0.05). VAS pain syndrome decreased  from 35.36 ± 24.71  mm to 16.44  ± 17.07  mm (p  = 0.0005). The global CIVIQ 20 quality of life index increased  by 25.3% compared to the initial parameters (p  =  0.0001), the VCSS index decreased  from 5.93  ± 1.79  points  to 4.79  ± 2.01  points  (p  = 0.0002).Conclusion. Sulodexide, causing a pronounced  clinical effect, is an effective and pathogenetically justified drug for the treatment of initial forms of chronic lower limb vein disease.